2006
DOI: 10.1021/ja057949b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Organization of Cholesterol in Unsaturated Phosphatidylethanolamines:  X-ray Diffraction and Solid State2H NMR Reveal Differences with Phosphatidylcholines

Abstract: The major mammalian plasma membrane lipids are phosphatidylcholines (PCs), phosphatidylethanolamines (PEs), and cholesterol. Whereas PC-cholesterol interactions are well studied, far less is known about those between PE and cholesterol. Here, we investigated the molecular organization of cholesterol in PEs that vary in their degree of acyl chain unsaturation. For heteroacid sn-1 saturated (palmitoyl), sn-2 unsaturated (various acyl chain) PEs, cholesterol solubility determined by X-ray diffraction was essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
78
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 52 publications
12
78
0
Order By: Relevance
“…They showed a DHAcontaining PC underwent a greater increase in molecular order upon adding cholesterol compared with a DHAcontaining PE ( Table 2 ). These results were in agreement with previous studies to show cholesterol was more soluble in n-3 PUFAs containing PCs than PEs ( 27 ). It is also important to note that the DHA-containing PC underwent a substantial increase in molecular order when exposed to cholesterol in the mixture with SM, which was consistent with the increase in membrane molecular order observed ex vivo when comparing cross-linked rafts with the absence of cross-linking with FO ( Fig.…”
Section: Fo Enhanced B-cell Activation In Response To Lps Stimulationsupporting
confidence: 93%
See 1 more Smart Citation
“…They showed a DHAcontaining PC underwent a greater increase in molecular order upon adding cholesterol compared with a DHAcontaining PE ( Table 2 ). These results were in agreement with previous studies to show cholesterol was more soluble in n-3 PUFAs containing PCs than PEs ( 27 ). It is also important to note that the DHA-containing PC underwent a substantial increase in molecular order when exposed to cholesterol in the mixture with SM, which was consistent with the increase in membrane molecular order observed ex vivo when comparing cross-linked rafts with the absence of cross-linking with FO ( Fig.…”
Section: Fo Enhanced B-cell Activation In Response To Lps Stimulationsupporting
confidence: 93%
“…Overall, the data were highly consistent with predictions from detergent-free model membrane studies in which PCs containing DHA were found to have higher solubility for cholesterol, and by implication to have more favorable interactions with rafts, than PEs containing DHA ( 27 ). We confi rmed this by comparing the order of cholesterol on the perdeuterated sn-1 chain on a DHA-containing PC (16:0-22:6PC-d 31 ) vs. a DHA-containing PE (16:0-22:2PE-d 31 ) in mixtures with SM (1:1) and SM/cholesterol (1:1:1), mimicking rafts, using 2 H NMR spectroscopy ( Table 2 ).…”
Section: B-cell Activation Of Naive Cd4supporting
confidence: 80%
“…Partition coefficients for cholesterol are also smaller in unilamellar vesicles composed of PC with DHA than less unsaturated chains [53]. We have provided unequivocal substantiation of poor affinity for the sterol by the greatly reduced solubility that was measured in PUFAcontaining membranes by x-ray diffraction and solid-state 2 H NMR [54]. In fact, we have shown that cholesterol sequesters to the bilayer center when forced to mix with PUFA chains in dipolyunsaturated lipids [55,56].…”
Section: Pufa's Aversion To Cholesterolmentioning
confidence: 54%
“…Fatty acid unsaturation may play an important role in the formation of domains since it is known that cholesterol prefers interaction with saturated lipids (Nakagawa et al, 1979;Rujanavech and Silbert, 1986;Smaby et al, 1997). More recently Stephen Wassall's laboratory studied interaction of cholesterol with polyunsaturated lipid species (Shaikh et al, 2006;Shaikh et al, 2004). Here our results on lateral organization in mixed bilayers composed of 18:0-22:6n3-PC/PE/PS/cholesterol are summarized.…”
Section: Lateral Membrane Organization In Hufa Lipid Mixturesmentioning
confidence: 85%